Development of Picture Storybooks To Strengthen the Profile of Pancasila Students for Early Childhood - napitupulu, cahaya afriani; Fitriani, Ignatia Imelda; Balimulia, Sophia Oktavia (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Palangka Raya, 2024)
This research aims to develop learning media including pictures storybooks for Strengthening the Character of early childhood in accordance with the Pancasila Student Profile. This book highlights elements and cultural values ​​of Central Kalimantan including characters, clothing, local food, local plants and local wisdom. The book developed contains 5 (five) stories referring to the 5 (five) themes of the Pancasila profile dimensions: devotion to God, Independence, Mutual cooperation, Global diversity, Critical reasoning and Creativity. The development model used in this research refers to the Borg & Gall model. The research involved experts to carry out validation tests, include design, language and children's story experts. Respondents consisted of early childhood education teachers. The instrument data used includes questionnaires and interview sheets. Responses from teachers and students are analyzed to measure the practicality of using the product. This research is expected to make a significant contribution to children's character education and strengthen the profile of Pancasila students among the younger generation as well as provide new insights for the development of interesting and useful learning media for young children. Apart from that, it also encourages collaboration between educators and experts in creating teaching materials that are in accordance with the curriculum.